Erwtensoep is geen borsóleves: Vormverschillen tussen Nederlandse en Hongaarse samenstellingen veroorzaken conceptuele verschillen - Banga, Arina (Acta Neerlandica, 2015)
The present study investigates whether form differences between Dutch and Hungarian influence the interpretations that speakers have. The Dutch plural suffix –en, for example erwt-en (‘pea-s’), is often homographic and homophonous with the linking element in noun-noun compounds, for example erwtensoep (‘pea + en + soup’). Hungarian, in contrast, has no such form correspondence. The interpretation of Dutch and Hungarian compounds was investigated. We found a difference between Hungarian speakers rating Hungarian modifiers and Dutch speakers rating Dutch modifiers: the plurality ratings for the number of peas in erwtensoep, was higher than those for the number of peas in of borsóleves. In addition, when rating Dutch compounds, native Hungarian speakers seem to rely more on form than native Dutch speakers.